RADIO FREQUENCY POWER AMPLIFIER SUBSYSTEM DESIGN FOR 5G WIRELESS COMMUNICATION - Azhari, Muhammad Tariq (IRC, 2019)

(untitled)
In a communication system, radio transceiver is one of the major systems. Radio frequency transceiver is a combination of transmitter and receiver. Inside the transmitter, there are a few major subsystem and one of them is power amplifier. Power amplifier is an important subsystem in wireless communication which is installed to increase the power to send the signal to the receiver. With high signal frequency, more power is needed by increasing the low-power signal to a high-power signal. Due to active component used in power amplifier, the noises are donated to the transceiver thus increasing the noise figure which concludes in making the power amplifier production increased to improve the efficiency and provides a good gain. The method in creating a much more affordable power amplifier is proposed by improvising the design of the power amplifier. This conclude in making a good power amplifier design to tweak the performance but with low cost production.